The Influence of Transformational Leadership, Transformational Leadership and Organizational Culture on Employee Performance With Job Satisfaction as Moderation at the Fajrul Iman Islamic Boarding School Patumbak Deli Serdang, North Sumatra - Fajar Rezeki Ananda Lubis (Institute of Computer Science (IOCS), 2022)
This study aims to partially analyze the effect of Transformational Leadership and Organizational Culture on employee performance, whether there is a moderating effect of work discipline between the independent variable and the dependent variable at the Fajarul Iman Islamic Boarding School Patumbak Deli Serdang, North Sumatra. where the sample is 32 people, the sampling technique uses the formula by Baley in Mahmud (2011, p. 159) which states that for research using statistical data analysis, the minimum sample size is 30. 32 people were used as research respondents. The variables used in this study were independent variables, moderating variables and dependent variables. In this study the independent variables are Transformational Leadership (X1) and Organizational Culture (X2). The dependent variable is Employee Performance (Y), while the Moderating variable is Work Discipline (Z). Data analysis used multiple linear regression test and path analysis. The results of the study indicate that partially transformational leadership has a significant effect on employee performance and organizational culture has a significant effect on employee performance. Simultaneously, the transformational leadership variable and the organizational culture variable have a significant and significant effect on the employee performance variable. Work discipline as moderation can affect transformational leadership and organizational culture on employee performance at the Fajarul Iman Islamic Boarding School Patumbak Deli Serdang, North Sumatra.